Reform Of Criminal Procedure - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 1979)
Before dealing with the present law of criminal procedure in Malaysia and suggesting in what ways it can be improved, it might be useful to look at two other systems, the Islamic system and the French or Continental system.